Sex-dependent changes in lipid metabolism, PPAR pathways and microRNAs that target PPARs in the fetal liver of rats with gestational diabetes - Fornes, Daiana (2018)
Gestational diabetes mellitus (GDM) is a prevalent disease that impairs fetal metabolism and development. We have previously characterized a rat model of GDM induced by developmental programming. Here, we analyzed lipid content, the levels of the three PPAR isotypes and the expression of microRNAs that regulate PPARs expression in the liver of male and female fetuses of control and GDM rats on day 21 of pregnancy. We found increased levels of triglycerides and cholesterol in the livers of male fetuses of GDM rats compared to controls, and, oppositely, reduced levels of triglycerides, cholesterol, phospholipids and free fatty acids in the livers of female fetuses of GDM rats compared to controls. Although GDM did not change PPARα levels in male and female fetal livers, PPARγ was increased in the liver of male fetuses of GDM rats, a change that occurred in parallel to a reduction in the expression of miR-130, a microRNA that targets PPARγ. In livers of female fetuses of GDM rats, no changes in PPARγ and miR-130 were evidenced, but PPARδ was increased, a change that occurred in parallel to a reduction in the expression of miR-9, a microRNA that targets PPARδ and was unchanged in the liver of male fetuses of GDM and control rats. These results show clear sex-dependent changes in microRNAs that target different PPAR isotypes in relation to changes in the levels of their targets and the differential regulation of lipid metabolism evidenced in fetal livers of GDM pregnancies.